The multimedia documentation of endangered and minority languages : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Linguistics at Massey University - Petterson, Robert (Massey University, 2002)
This thesis examines the impending loss of linguistic diversity in the world and advocates a change in emphasis in linguistic research towards the documentation of minority and endangered languages. Various models for documentation are examined, along with some of the ethical issues involved in linguistic research amongst small groups, and a new model is proposed. The new model is centred around the collection of a wide variety of high-quality data, but includes the collection of other related materials that will be of particular use and interest to the ethnic community. The collected data and other materials are then structured as an internet-ready multimedia documentation designed for use by the ethnic community as primary audience, while still catering for the needs of linguistic researchers worldwide. A pilot project is carried out using the model.
Keywords: Computational linguistics; Interactive multimedia; Kairi language